DYSTOKIA IN A MARATHWADI BUFFALO DUE TO MONSTER WITH ARTHROGRYPOSIS - KUMBHAR, U B; PATIL, A D; MORE, R M; GACCHE, S M (The Indian Journal of Animal Reproduction, 2023)
A female monster with Arthrogryposis, micromelia, & atresia ani, placed on record in a Marathwadi buffalo.
Keywords: Monster; Arthrogryposis; Micromelia; Atresia; Buffalo